1999
DOI: 10.2307/541401
|View full text |Cite
|
Sign up to set email alerts
|

Powwow Patter: Indian Emcee Discourse on Power and Identity

Abstract: Emcees of southern Plains Indian powwows are distinctive verbal artists and agents in the continuing negotiation of Indian identity. Their formal announcements and jovial patter construct an overtly "Indian" space and time while fostering discourse on ethnicity, a discourse that carries over into other settings through traditional transmission of the emcee’s jokes and observations. Examples are drawn from 15 years of fieldwork at Comanche, Kiowa, Pawnee, and Alabama-Coushatta events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The performer is embedded in the narrative being made visible or performed. This is not to say that performers are pure or even noble; on the contrary, many folklore field studies indicate that the best folklore performers have a certain disreputability associated with their prowess as storytellers or talkers (Bauman & Ritch, 1996;Gelo, 1999). But these particular folklore performers have the same commitment to the narrative, the same propensity for lived action, and the same moral responsibility to their community as all others do.…”
Section: Communication and Folklore: Co-informing Perspectivesmentioning
confidence: 92%
“…The performer is embedded in the narrative being made visible or performed. This is not to say that performers are pure or even noble; on the contrary, many folklore field studies indicate that the best folklore performers have a certain disreputability associated with their prowess as storytellers or talkers (Bauman & Ritch, 1996;Gelo, 1999). But these particular folklore performers have the same commitment to the narrative, the same propensity for lived action, and the same moral responsibility to their community as all others do.…”
Section: Communication and Folklore: Co-informing Perspectivesmentioning
confidence: 92%
“…Their easy humor is often a surprise to people not familiar with American Indians (who may be expecting people and situations more closely conforming to their misconceptions and stereotypes), especially at a powwow, an event such visitors expect to be serious ceremony rather than social and celebratory. Existence of intentional humor in dance is noted by Toelken (1991) and Toelken and Brown (1987), and Gelo (1999) notes the typically humorous discourse of the emcee. The witty and often ironic humor of contemporary Indianness draws upon long standing humorous traditions of the many American Indian nations and is a unifying element in intertribal contexts (Lincoln, 1993;Pratt, 1998).…”
Section: Humor To Facilitate Intercultural Educationmentioning
confidence: 93%
“…Programs and emcee commentary explicitly encourage a sense of solidarity among all listeners (participants and visitors) and also are reminded that the solidarity is in Indian space (Gelo, 1999). Thus the hegemonic-nondominant power structure is suspended, even reversed, within the powwow space.…”
Section: Utilization Of Printed Programs and Emcee To Facilitate Crosmentioning
confidence: 95%
See 1 more Smart Citation
“…Gelo (1999) has suggested that the location of the market at the edge of the public powwow space reflected its lack of attention to the more central powwow activities taking place in the dance arena because of its distance from the emcee's voice. Elsewhere, I offer a reconceptualization of this valuation of the market's spatial position and suggest that the market is central, not peripheral, to the constitution of the powwow as a Native sociospatial place (Gagnon, 2013).…”
Section: The Powwow Its Market and The Indian Art Field Of Culturalmentioning
confidence: 98%